Law, history, and the social sciences: Intellectual traditions of late nineteenth- and early twentieth-century Europe - Getzler, J (Oxford University Press, 2012)
The purpose of this essay is to describe and analyse the historiography of law and the economy in Europe in the late nineteenth and earlier twentieth centuries. Three major themes or approaches can be identified within this intellectual history. The first is a sociological interest in the nature and evolution of modernity in society. Here the contested concept of ‘modernity’ is used to mean the emergence of a society and culture where personal identities and social practices and norms are no longer determined primarily by communal tradition but are to some degree chosen. The second approach is political, and centres on the emergence of the state as a chief framework for national and communal life, replacing local, religious, and kinship institutions. The third approach is economistic, and searches for the legal, governmental, and institutional factors that revolutionized the productive capacity of the economy and led to European domination of the world by 1900.